2019
DOI: 10.7150/jca.32467
|View full text |Cite
|
Sign up to set email alerts
|

Risk Prediction for Early Mortality in Patients with Newly Diagnosed Primary CNS Lymphoma

Abstract: Background: Overall survival of patients with primary CNS lymphoma (PCNSL) has improved since the introduction of immunochemotherapy. However, up to 10-15% of PCNSL patients still die shortly after diagnosis. In the present study, we aimed to investigate the risk factors of early mortality (death within 60 days after diagnosis) in patients with PCNSL. Methods: We included newly diagnosed PCNSL patients in a tertiary medical center in Taiwan between January 1, 2002 and May 31,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…ECOG of 2 was used as cutoff according to prior studies of PCNSL . Similarly, age of 80 years was chosen as cutoff according to previous research showing 80 years as a potential risk factor for mortality in patients with systemic diffuse large B‐cell lymphoma as well as PCNSL . Cutoff values of hemoglobin, C‐reactive protein, and bilirubin levels were 11.85 g/dL, 2.94 mg/dL, and 0.52 mg/dL, respectively, which were correlated with clinical outcomes in one previous study of diffuse large B‐cell lymphoma .…”
Section: Methodsmentioning
confidence: 99%
“…ECOG of 2 was used as cutoff according to prior studies of PCNSL . Similarly, age of 80 years was chosen as cutoff according to previous research showing 80 years as a potential risk factor for mortality in patients with systemic diffuse large B‐cell lymphoma as well as PCNSL . Cutoff values of hemoglobin, C‐reactive protein, and bilirubin levels were 11.85 g/dL, 2.94 mg/dL, and 0.52 mg/dL, respectively, which were correlated with clinical outcomes in one previous study of diffuse large B‐cell lymphoma .…”
Section: Methodsmentioning
confidence: 99%
“…Lin et al reported that age ≥ 80 years and involvement of the basal ganglia were identified as independent risk factors of early mortality. 41 On the other hand, the study conducted in Brazil revealed that older age, male gender and white race were associated with higher mortality in lymphoma patients. 42 Therefore, effective interventional strategies should be implemented among comorbid and advanced-stage patients to reduce mortality and extend survival time among all the selected malignancies in the study setting.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, previous studies found that older age and pretreatment PS are significant prognostic factors. [ 2 3 5 6 10 11 13 14 ] Most previous studies defined older age as >60 years,[ 3 6 13 16 17 18 ] whereas others used >50 years as the cut off. [ 2 5 11 14 ] In our study, older age was a significant predictor of poor outcomes in the univariable analysis, and age was a poor prognostic factor, but not significant, in the multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this study found that patients had a short survival time with a median overall survival of 7 months compared with previous studies that found that the median overall survival of PCNSL patients was higher and ranged from 9 to 100 months. [3,5,7,10,12,[14][15][16] Based on our knowledge, the different survival rates were primarily influenced by the patient's status and treatment options. A patient's preoperative status plays a significant role in determining treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation